EFFECTIVE USE OF LABOR RESOURCES IN A COMPETITIVE MARKET - Тоштемиров Иброхимжон Муродил угли (Ecomind Press, 2025)
In the rapidly changing and competitive global market, the effective use of labor resources is crucial for ensuring sustainable economic growth and social stability. This article provides an in-depth study of strategies and mechanisms for optimizing labor resources, taking into account global economic trends and modern challenges. Empirical data are presented, supported by concrete examples of successful practices from various countries, including Uzbekistan, with emphasis on adapting international experience to national conditions. The article also offers recommendations for improving personnel management and increasing labor productivity in an increasingly competitive environment.
Keywords: Labor resources, competitive market, efficiency, personnel management, economic growth, digitalization.